Devaluation, Oil Price Shock and Consumer Price Inflation: Evidence from Markov Autoregressive Regime Switching Model - David Umoru; Salisu Shehu Umar; Beauty Igbinovia (Romanian Economic Journal, 2025)
Decreasing trends in the external worth of most currencies and an oil price surge have been accompanied by a persistent increase in food prices and transportation costs. In 2023, Sub-Saharan Africa (SSA) had a growth rate of 3.3 percent (IMF, 2023), yet the region experiences long-lasting external shocks in addition to domestic shocks. The goal of this study is to clarify the dynamic effects of devaluation of exchange rates and oil price shocks on the prices of food and fuel consumption in eleven SSA emerging nations while also examining the causality's direction. The study also seeks to ascertain whether there is a threshold for oil prices based on the relationship between oil prices, currency rates, and food consumption. We estimated the Markov Autoregressive Regime Switching Model (MARSM) with monthly data from 2000Q1 to 2024Q2. The research findings provide an informed basis for re-assessing the monetary policy rate in order to control inflation in Nigeria. In particular, the study establishes that the conventional theoretic view of monetary policy transmission, whereby higher interest rates translate to reductions in inflation, is misleading for SSA. The study established the presence of a domino effect, which embraces excessive depreciation of local currencies, causing high consumer price inflation that leads to rising costs of living in the midst of a foreign exchange shortage. For a sensitivity analysis, we disaggregated the consumer price inflation rate into food inflation and fuel consumption price to have food CPI and fuel CPI and estimated the panel GMM model for our panel of ten nations. The importance of transition probabilities in comprehending food price inflation validates the model's validity. The results validate the presence of a significant causation effect of currency depreciation, oil price surges, and interest rate differentials on the price of food and fuel in SSA. It is advisable to take into consideration the established fact that the amount of surplus reserves in emerging nations serves as the primary anchor for their currency rates. Therefore, exchange rate stability might be attained even in the face of declining oil revenue by making a deliberate effort to diversify the economy's export base and expand infrastructure.